Exploring the impact of community service experiences on social responsibility of adolescents in private schools in Egypt - El-Tantawy, Moaz Osama (AUC Knowledge Fountain, 2017)
With rise of modern societies and emerging market economies, scholars and socially- minded intellectuals started to express their concerns about negative repercussions on the social fabric of the human society. Significant amounts of research wrote about the gradual decline in social cohesion between different social classes. This decline is reasoned by multiple economic and political factors that some scholars link to capitalist polices. Many solutions were proposed to decrease this social stratification globally and in Egypt, through developing the sense of social responsibility among community members. One of the proposed solutions is community service programs. This study examines the effect of community service programs on the development of sense of social responsibility among private school students in Egypt. Methodologically, the study followed a qualitative approach. Focus group discussions took place with twenty-five students from two different schools to explore the relation between participation in community service programs and the development of a sense of social responsibility. Also, semi-structured individual interviews were conducted with the four teachers who served as supervisors of different community service programs, in the school to uncover their perceptions about the impact of the programs on students. Findings of this study document the positive impact of community service programs on students socially, morally and personally. More importantly, a positive correlation was drawn between social responsibility and the extent of involvement in community service programs.